A microscopic view on the electrochemical deposition and dissolution of Au with scanning electrochemical cell microscopy – Part I. (20th March 2023) - Bernal, Miguel; Torres, Daniel; Parapari, Sorour Semsari; Čeh, Miran; Rožman, Kristina Žužek; Šturm, Sašo; Ustarroz, Jon
Abstract: The nucleation and dissolution of gold nanoparticles (NPs) on a glassy carbon substrate have been studied with a local electrochemical approach based on Scanning Electrochemical Cell Microscopy (SECCM). By performing hundreds of locally-resolved voltammograms, a distribution of responses for nucleation was found when scanning multiple regions of the substrate, addressing experimentally the statistical nature of the nucleation and growth process at the micro-scale. Moreover, the confinement of the electrochemical cell to the SECCM meniscus enables us to resolve a diversity of events during the electrochemical dissolution of previously electrodeposited NPs, characterized as current spikes during the voltammetric scans. These current events do not manifest in the macro-scale due to the averaging of the electrochemical response over the large electrode area and reveal previously untapped information from the electrochemical nucleation, growth, and dissolution of supported metal nanoparticles. This approach opens up new opportunities for the rational design (electrodeposition) of functional nanostructured materials and the evaluation of their durability under electrochemical polarization (resistance to electrodissolution). The ability to study these considering the heterogeneous nature of the supports and the differences within nanomaterial ensembles is essential for applications in electrochemical conversion and storage.